Distribution of authigenic and allogenic fractions in recent lake sediment: Isotopic and chemical compositions - Jadranka Barešić; Nada Horvatinčić; Polona Vreča; Andreja Sironić (Acta Carsologica, 2012)
Recent sediments in Lake Kozjak, in the Plitvice Lakes National Park, Croatia, were used to study the impact of the material delivered to the lake sediment via Rječica Brook. Sediment cores, top 40 cm, were taken near the mouth of the Rječica Brook at three locations in the lake at different distances from the shore, water depth 2-9 m and analyzed using different isotopic and chemical methods. Sediment depth profiles of the following parameters were obtained: organic and carbonate fraction, C/N analyses of organic fraction, 14C activity (a14C) and d13C values of carbonate (d13Ccarb) and organic fraction (d13Corg) and d15N of total nitrogen. The results were compared with sediment core collected in the middle of Lake Kozjak, water depth 21 m. Distribution of organic matter, C/N values, d13Corg and d13Ccarb in sediment profiles showed strong influence of terrestrial organic and carbonate fraction run-off via Rječica Brook which decreased rapidly in the direction of the open lake. The sedimentation rate as well as the ratio of allogenic and authigenic fraction in sediments was estimated. Lower d13Corg values in surface sediments might be a consequence of the increase in algal productivity but might also be a contribution of fossil fuel combustion. The anthropogenicaly induced 14C in the atmosphere in 1963/64 is visible though shadowed in sediments.